Research on the osteogenesis and biosafety of ECM–Loaded 3D–Printed Gel/SA/58sBG scaffolds - Tan, Guozhong; Chen, Rongfeng; Tu, Xinran; Guo, Liyang; Guo, Lvhua; Xu, Jingyi; Zhang, Chengfei; Zou, Ting; Sun, Shuyu; Jiang, Qianzhou (Frontiers in Bioengineering and Biotechnology, 2022)
Employing scaffolds containing cell–derived extracellular matrix (ECM) as an alternative strategy for the regeneration of bone defects has shown prominent advantages. Here, gelatin (Gel), sodium alginate (SA) and 58s bioactive glass (58sBG) were incorporated into deionized water to form ink, which was further fabricated into composite scaffolds by the 3D printing technique. Then, rat aortic endothelial cells (RAOECs) or rat bone mesenchymal stem cells (RBMSCs) were seeded on the scaffolds. After decellularization, two kinds of ECM–loaded scaffolds (RAOECs–ECM scaffold and RBMSCs–ECM scaffold) were obtained. The morphological characteristics of the scaffolds were assessed meticulously by scanning electron microscopy (SEM). In addition, the effects of scaffolds on the proliferation, adhesion, and osteogenic and angiogenic differentiation of RBMSCs were evaluated by Calcein AM staining and reverse transcription polymerase chain reaction (RT–PCR). In vivo, full–thickness bone defects with a diameter of 5 mm were made in the mandibles of Sprague–Dawley (SD) rats to assess the bone regeneration ability and biosafety of the scaffolds at 4, 8 and 16 weeks. The osteogenic and angiogenic potential of the scaffolds were investigated by microcomputed tomography (Micro–CT) and histological analysis. The biosafety of the scaffolds was evaluated by blood biochemical indices and histological staining of the liver, kidney and cerebrum. The results showed that the ECM–loaded scaffolds were successfully prepared, exhibiting interconnected pores and a gel–like ECM distributed on their surfaces. Consistently, in vitro experiments demonstrated that the scaffolds displayed favourable cytocompatibility. In vitro osteogenic differentiation studies showed that scaffolds coated with ECM could significantly increase the expression of osteogenic and angiogenic genes. In addition, the results from mandibular defect repair in vivo revealed that the ECM–loaded scaffolds effectively promoted the healing of bone defects when compared to the pure scaffold. Overall, these findings demonstrate that both RAOECs–ECM scaffold and RBMSCs–ECM scaffold can greatly enhance bone formation with good biocompatibility and thus have potential for clinical application in bone regeneration.